PENGARUH DISIPLIN KERJA TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA PEGAWAI DINAS PERHUBUNGAN KOTA BALIKPAPAN - Yuliani, Tutik; Hadiyatno, Didik; Ariani, Misna; Yusuf, Tamzil; Saraswati, Wiwik; Natha Symha Murti, Sonya (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to determine the direct influence of work discipline and motivation variables on the performance of Balikpapan city transportation service employees, as well as to determine the indirect effect of work discipline on performance with motivation as a mediating variable for Balikpapan city transportation service employees. This research used a sample of 53 respondents with a questionnaire data collection method and analysis tools assisted by PLS software. The results show that (1) work discipline directly has a positive and significant effect on the motivation and performance of Balikpapan city transportation service employees; (2) motivation directly has a positive and significant effect on the performance of Balikpapan city transportation service employees; (3) Indirectly, work discipline influences the performance of transportation service employees by mediating motivation